Gene Therapy Revolution: Recent Advances and Modern Biomedical Laboratory Techniques - Antoni, Marcel; Susilowati, Rina Priastini (Jurnal MedScientiae, 2024)
Genetic therapy is a revolutionary innovation in the medical world that aims to treat or prevent diseases through the modification of the patient's genetic material. This literature review examines the latest advances in genetic therapy, including the biomedical laboratory techniques used. Techniques such as Polymerase Chain Reaction (PCR), DNA sequencing, CRISPR-Cas9, and Prime Editing have provided the ability to modify genes with high precision. Genetic therapy has shown success in various diseases, including monogenic genetic diseases such as hemophilia and Duchenne Muscular Dystrophy, as well as cancer through Chimeric Antigen Receptor T-cell (CAR-T) therapy. Additionally, research shows the potential of genetic therapy in addressing complex diseases such as cardiovascular disease and diabetes, as well as in regenerative treatment for degenerative diseases like Parkinson's. Despite being promising, challenges related to ethics, safety, and accessibility still need to be addressed. Case studies indicate that although there are many successes, there are still obstacles to be overcome to improve the effectiveness and safety of this therapy. This literature review concludes that genetic therapy has great potential to become an important pillar of modern treatment in the future, provided that further research and development are needed to overcome the various existing barriers.